2002
DOI: 10.1086/338638
|View full text |Cite
|
Sign up to set email alerts
|

Abacavir Expanded Access Program for Adult Patients Infected with Human Immunodeficiency Virus Type 1

Abstract: Expanded access programs (EAPs) provide medication to patients with life-threatening, treatment-refractory illnesses before regulatory approval and allow the acquisition of safety information. A 2-part, multisite EAP to evaluate abacavir, a carbocyclic nucleoside reverse-transcriptase inhibitor for use in combination antiretroviral therapy, was conducted. The EAP involved >13,000 adults infected with human immunodeficiency virus type 1 (HIV-1) who no longer responded to commercially available treatment regimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 11 publications
(12 reference statements)
1
11
0
Order By: Relevance
“…27 In our study, we observed no significant change in Framingham 10-year CHD risk scores, hsCRP, and IL-6 concentrations, declines in Lp-PLA2 activity (hypothesized to correlate with reductions in the atherosclerotic process 38 ), and improvements in the total cholesterol/HDLcholesterol ratio over 144 weeks with ABC/3TC + ATVcontaining regimens. These results are consistent with those from many studies that have evaluated ABC-containing regimens and failed to observe an increase in estimated cardiac risk, [18][19][20][21][22]46 and contrast with findings from two recent observational cohorts analyses that reported a statistically increased incidence in MI in HIV-infected patients receiving ABC-based therapy with various third agents. 23,24 For our study, as with other studies, confounding risk factors such as recreational drug use or alcohol consumption may impact the findings but may be difficult to assess.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…27 In our study, we observed no significant change in Framingham 10-year CHD risk scores, hsCRP, and IL-6 concentrations, declines in Lp-PLA2 activity (hypothesized to correlate with reductions in the atherosclerotic process 38 ), and improvements in the total cholesterol/HDLcholesterol ratio over 144 weeks with ABC/3TC + ATVcontaining regimens. These results are consistent with those from many studies that have evaluated ABC-containing regimens and failed to observe an increase in estimated cardiac risk, [18][19][20][21][22]46 and contrast with findings from two recent observational cohorts analyses that reported a statistically increased incidence in MI in HIV-infected patients receiving ABC-based therapy with various third agents. 23,24 For our study, as with other studies, confounding risk factors such as recreational drug use or alcohol consumption may impact the findings but may be difficult to assess.…”
Section: Discussionsupporting
confidence: 90%
“…While atazanavir (ATV) has demonstrated little dyslipidemic impact as compared with certain other protease inhibitors (PIs), there are concerns regarding ritonavir (/r)-boosted PI regimens as potentially increasing CHD risk, although whether this would be associated with any change in inflammatory biomarker concentrations is unclear. [13][14][15][16] Abacavir (ABC) is a generally well-tolerated nucleoside reverse transcriptase inhibitor (NRTI) that has been used in combination antiretroviral regimens since the 1990s, 17 and while the majority of studies [18][19][20][21][22] have not demonstrated an increased ABC-attributable CHD risk in the absence of confounding factors, two recent analyses of observational cohorts 23,24 reported a statistically increased incidence in MI in HIV-infected patients receiving ABC-based therapy with various third agents.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients who reported ABC HSR were enrolled in GSK's ABC Expanded Access protocol, which allows patients the opportunity to gain access to medicines prior to regulatory approval. 7,8 Because the symptoms of ABC HSR overlap with those of adverse events associated with other anti-retroviral HIV medicines or other clinical conditions, establishing the accuracy of the clinical diagnosis of ABC HSR was challenging. Furthermore, during the conduct of the ABC Expanded Access protocol, GSK's understanding of HSR grew and guidance to investigators for the diagnosis and management of HSR evolved.…”
Section: Introductionmentioning
confidence: 99%
“…2 Current clinical uses of TMPeSMX include urinary, respiratory and gastrointestinal infections as well as prevention of infections in immunocompromised patients. 2 More frequent side effects of TMPeSMX are mild gastrointestinal symptoms, dose related bone marrow effects, liver failure, skin rash, sepsis-like and hypersensitivity reactions. 3 Skin rash or more severe skin reactions such as exfoliative dermatitis, the Stevens Johnson Syndrome, the Lyell Syndrome or toxic epidermal necrolysis, have been rarely reported.…”
Section: Trimethoprimesulfamethoxazole Induced Erythrodermic Psoriasismentioning
confidence: 99%
“…Usually, patients present fever (80%), skin rash (70%) and asthenia (40%); sometimes, gastrointestinal (as nausea, vomiting, diarrhoea, and abdominal pain) or respiratory symptoms were reported; in 10% of the patients, myalgias, pains in the joints or myopathic symptoms have been referred. 2 Symptoms related to the hypersensitivity reaction worsen with continued therapy and usually improve within 24e72 h of abacavir discontinuation. Re-challenge with abacavir, after a hypersensitivity reaction, typically results in recurrence of symptoms within hours, with the potential to induce a more severe clinical syndrome with increased risk of life-threatening hypotension and death.…”
mentioning
confidence: 99%